2021
DOI: 10.3390/diagnostics11071264
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of PET/CT with 18F-FDG in Patients with Differentiated Thyroid Carcinoma after Radioiodine Therapy: An Italian Multicenter Study

Abstract: Background: our aim was to assess the diagnostic performance and clinical impact of 18F-FDG PET/CT in patients with differentiated thyroid carcinoma (DTC), previously treated with surgery and radioiodine therapy (RAI). Methods: patients subjected to 18F-FDG PET/CT for suspected DTC recurrence in three Italian nuclear medicine units were evaluated. Two different clinical settings were identified: clinical setting 1 included patients (n = 40) that were enrolled according to the American Thyroid Association guide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Among these, ultrasound was employed and sometimes associated with fine-needle aspiration biopsy (FNAB), as well as nuclear medicine exams, and in particular, 131 I-SPECT/CT, more recently applied in the clinical field [48][49][50][51][52], and sequential serum thyroglobulin and AbTg assays in the two groups of patients and AbTPO in PC/HT cases. In general, CT and MRI, and when the carcinomas are poorly differentiated by 18 F-FDG PET/CT [53], represented the other diagnostic imaging highly sophisticated procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, ultrasound was employed and sometimes associated with fine-needle aspiration biopsy (FNAB), as well as nuclear medicine exams, and in particular, 131 I-SPECT/CT, more recently applied in the clinical field [48][49][50][51][52], and sequential serum thyroglobulin and AbTg assays in the two groups of patients and AbTPO in PC/HT cases. In general, CT and MRI, and when the carcinomas are poorly differentiated by 18 F-FDG PET/CT [53], represented the other diagnostic imaging highly sophisticated procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Larg et al showed that [ 18 F]FDG-PET/CT can influence clinical decision making for DTC with elevated hTg levels and a negative 131 I WBS, leading to a change in treatment strategy in 33.5% (58/173) of cases [17]. Filippi et al demonstrated an impact on clinical patient management in 42.4% of cases in a similar setting (DTC with elevated hTg levels and a negative 131I whole-body scan) [34]. Furthermore, it has been demonstrated that certain PET/CT parameters (total MTV and total TLG) possess a prognostic predictive value under specific conditions [35].…”
Section: Discussionmentioning
confidence: 99%
“…FDG PET imaging has become increasingly important in management of patients with thyroid cancer, with FDG avid disease associated with poor prognosis 16–22 . FDG PET imaging have a role in detecting recurrence or persistent disease in both patients with negative WBS and elevated Tg (>10 ng/ml), and those with Tg < 10 ng/ml after initial treatment 21,23–26 . The degree of FDG avidity has been associated with poor survival 5,17,25,27,28 and associated with poor response to RAI 29 .…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22] FDG PET imaging have a role in detecting recurrence or persistent disease in both patients with negative WBS and elevated Tg (>10 ng/ml), and those with Tg < 10 ng/ml after initial treatment. 21,[23][24][25][26] The degree of FDG avidity has been associated with poor survival 5,17,25,27,28 and associated with poor response to RAI. 29 In our cohort, I-PET [3] identified patients who had become refractory to RAI with high rates of progression; these patients were more likely to receive a mutlikinase inhibitor and were at increased risk of death from their disease.…”
Section: Discussionmentioning
confidence: 99%